MEMBANGUN PENDIDIKAN KARAKTER ANAK BERBASIS BUDAYA KEARIFAN LOKAL DALAM MENANAMKAN NILAI KEBANGSAAN DI SEKOLAH - husin, rany chairunnisa (PSGA LP2M IAIN Pontianak, 2023)
Planting character values is a process of developing culture in a natural way that is inherent in the pattern of work life that must be done. Implementation of character education in schools for example as part of education reform, character education can be likened to a tree that has four important parts, namely roots, stems, branches, and leaves. The roots of reform as a philosophical foundation (foundation) for the implementation of character education must be clear and understood by the community organizers and education practitioners. Building character education in schools through local wisdom culture contains values that are relevant and useful for education. Therefore, character education based on local wisdom can be done by revitalizing local culture. Building student character can be done throughout the learning process. In every learning process we can always slip the load of values of honesty, courage, perseverance and tenacity, self-confidence, diligent study and work, respect for parents and teachers, respect and love others, live tough not knowing the words of surrender and positive attitude another. Thus our job is to find the right numbers in the right order, so we can open the door to success. There is no specific recipe that makes people successful, except trying hard in the form of hard work, study hard, have a high curiosity, discipline, and resilient. Local culture which becomes the main can to develop children's character in the learning process at school. The most important thing is our sincerity as educators to always educate with the heart. Educating with heart will prioritize the formation of positive attitudes such as; Honest, tolerant, trustworthy, mutual and caring, optimistic, confident, tough and others.